PROBLEM OF ISIS’S QUR’ANIC INTERPRETATIONS AND CLAIM OF THE IMPLEMENTATION OF SHARIA LAW - Aulassyahied, Qaem (IJISH (International Journal of Islamic Studies and Humanities), 2018)
This paper discusses the problem of ISIS’s Qur’anic interpretations regarding the implementation of sharia law and the concept of jihad. It is essential to address this topic because the self-proclaimed Caliphate have claimed that their barbaric actions such as indiscriminate killing of civilians, plundering, and declaring other Muslims as apostates are based on Qur’anic verses. They also consider these actions as part of the jihad to uphold sharia law. This paper argues that there are two main problems in ISIS’s Qur’anic interpretations, namely (1) cherry picking Qur’anic verses that support their causes. According to the principles of Qur’anic exegesis (ushul al-tafsīr), this method of interpretation is certainly not justified because it will lead to the partial understanding of the message of the Qur’an; (2) attempting to enforce the sharia law without proper understanding of the law. As a result, ISIS’s implementation of sharia goes against the ultimate purposes of the sharia (maqāsid al-sharī’ah).